Application of a complex system for optical monitoring of technical condition of building structures with external composite reinforcement - M. Yu. Fedotov; A. A. Kalgin; E. E. Shmoilov; P. D. Kapyrin; O. A. Kornev (Vestnik MGSU)
Introduction. The relevance of using modern methods for continuous assessment of the actual condition of road and railway bridges, industrial and other engineering structures is substantiated. The results of wide application of optical method for continuous control of technical condition of engineering structures under real operating conditions are presented.Materials and methods. Using quasi-distributed fibre-optic sensors based on fibre Bragg gratings. This paper presents experience in the application of fibre-optic monitoring systems, which generally include — a set of fibre-optic sensors (FOS), built on different physical principles, — multi-channel devices for their interrogation (interrogators), — built-in special software (Open source software) designed for collecting, processing and visualizing monitoring data. Among the most well-known developers and suppliers of composite systems for external reinforcement based on carbon reinforcing fibres, it is worth mentioning foreign and domestic materials under the trademarks of MasterBrace (BASF SE, Germany), SikaWrap (Sika Group, Germany), Torayca (Toray Industries, Japan), FibARM ( JSC “Prepreg-SСM”, Russia), S&P (JSC “Triada-Holding”, Russia) and others. Some of the first regulatory documents establishing requirements for organizing monitoring in the construction industry are MGSN 4.19–2005, GOST R 22.1.12–2005, MRDS-02–08 and some others.Results. It was established that one of the most promising technologies for restoration of damaged structures is the application of external reinforcement systems made of polymer composite materials based on carbon fibres and cold-curing polymer binders. The experience of practical application of composite systems of external reinforcement of engineering structures is described.Conclusions. It is shown that the results of such control allow timely revealing the reduction of bearing capacity, occurrence of operational damages, planning repair measures that the application of fibre-optic methods and means of continuous diagnostics and composite systems of external reinforcement in a complex, allows to provide safety of operation of engineering constructions in real conditions.